(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Aerosol jet printing is a process under the umbrella of additive manufacturing for conformably putting electronics on unconventional substrates. The project highlights potential of aerosol jet to print conformal and flexible antenna device. Polycaprolactone (PLC) polymer is chosen for it’s biodegradable nature. A flexible scaffold is fabricated using melt-drawn process and pre-treated with gelatin-based hydrogel to reduce surface roughness. Carbon nanotube (CNT) nanomaterial ink is printed directly on the treated PLC, and antenna characteristics are measured.